Th1rteen r3asons why : a novel - Asher, Jay, 1975- (New York : Razorbill, 2007)
When high school student Clay Jenkins receives a box in the mail containing thirteen cassette tapes recorded by his classmate Hannah, who committed suicide, he spends a bewildering and heartbreaking night crisscrossing their town, listening to Hannah's voice recounting the events leading up to her death.
Keywords: Suicide -- Fiction; High schools -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction; Fiction